Opportunities and challenges of digital fabrication applied to field work in biological projects - Quesada, Luis Diego Gómez (Edelweiss Applied Science and Technology, 2025)
This article documents the use of digital fabrication technologies throughout the stages of developing a prototype designed for field use. The device was developed to collect data on the feeding patterns of hummingbirds in the Cerro de la Muerte area in the Talamanca mountain range of Costa Rica, considering the importance of these birds as pollinating agents. This design and development process, carried out in a Fabrication Laboratory, focuses on digital fabrication prototyping, with multiple iterations and modifications. Through the development stages of the device, the opportunities and challenges of applying digital fabrication to a project with biological impact are illustrated, along with insights on how to better approach future projects of this nature.